CONSTRUCTING GLOBAL ‘WARS WITHOUT END’: Vocabularies of Motive and the Structure of Permanent War - Asadi, Muhammed (Qualitative Sociology Review, 2021)
My purpose in this paper is to link the larger social context that structurally necessitates „wars without end” perpetrated by the U.S. elite with the rhetoric that legitimizes them so as to sociologically situate the rhetoric, the vocabularies of motive within a historically formed war-centric social structure that reveals an easily discernible pattern in the use of language. I consider Franklin D. Roosevelt’s speech of December 8, 1941 announcing U.S. entry into World War II to be the rhetorical “Master Frame”, the blueprint in this regard that was subsequently incorporated by later presidents to justify all wars without end. I compared dissected components of this rhetorical Master Frame to war speeches made by different U.S. presidents in the pre- and post-World War II era to reveal the qualitative difference between war rhetoric of a peace-time social structure where war is an aberration and the permanent war based social structure of the post-World War II U.S., when war became the taken for granted norm.